The influence of different implements on kinematics and kinetics compared to mens javelin throw - Koehler, H.-P.; Witt, M. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The aim of the study was to investigate the influence of different throwing devices on the kinematics and kinetics of the throwing arm. Therefore, six experienced athletes threw six different implements (five balls, one javelin) with different masses. Retroreflective marker data were captured using a 12-camera infrared system. The results show significant differences between the implements, where lighter implements achieve higher release speeds. Furthermore, differences in the shoulder external rotation angle, the angular velocities of shoulder internal rotation and elbow extension, as well as the moments at the shoulder and elbow could be shown. It can be concluded that balls of different masses have similar kinematics and kinetics and can therefore be used to train speed and strength aspects of the javelin throw while using lower run-up speeds.